Catalytic Pyrolysis of Reed for Bio-Oil and Biochar Production - Andreea-Luiza Mirt; Alexandru Vlaicu; Mihaela Ciltea-Udrescu; Grigore Psenovschi; Gabriel Vasilievici (Proceedings, 2023)
Indigenous available common reed stalk has been investigated as potential feedstock for pyrolysis at temperatures between 400 and 600 °C. The performance of this type of feedstock was evaluated in terms of yield towards pyrolysis products. The two main products of interest, biochar and bio-oil, have been characterized through textural analysis and GC-MS, respectively, with the relation between temperature and characteristics being highlighted. Increasing the pyrolysis temperature led to smaller yields in biochar and an improvement of textural properties, such as specific surface area and total pore volume, while the composition of the bio-oil changed significantly as the temperature increased.